2015
DOI: 10.5935/1415-2762.20150012
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning in a Virtual Environment: Nursing Students’ Attitude

Abstract: RESUMOObjetivou-se avaliar uma hipermídia como estratégia de ensino, a aprendizagem em ambiente virtual e a atitude de acadêmicos de Enfermagem para o ensino on-line das doenças sexualmente transmissíveis. Trata-se de estudo quase experimental, do tipo antes e depois, realizado com 28 acadêmicos de Enfermagem de uma universidade pública da região Nordeste do Brasil. Os participantes da amostra foram selecionados por conveniência. Para a coleta de dados, foi disponibilizada uma hipermídia hospedada no ambiente … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 14 publications
0
13
0
8
Order By: Relevance
“…their performance and access to the virtual environment in order to commit to their learning, because freedom of access can result in false feeling of ease and lack of need to comply with hours of study (27) . Innovative learning is the main way for exercising autonomy, considered as a way to understand and work positively in addition to the prevailing context.…”
Section: Discussionmentioning
confidence: 99%
“…their performance and access to the virtual environment in order to commit to their learning, because freedom of access can result in false feeling of ease and lack of need to comply with hours of study (27) . Innovative learning is the main way for exercising autonomy, considered as a way to understand and work positively in addition to the prevailing context.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out with Nursing students in Pernambuco showed a weighted average of 0.91 for the information exchange item with colleagues and professors. 11 Thus, rhythm, constancy of interaction and feedback between student-tutor, group-tutor and also encouragement with positive and altruistic messages are fundamental to create commitment to the educational process. 27 Interaction in a VLE is essential to shorten geographical and physical barriers, therefore, chat rooms can be used as online meeting spaces.…”
Section: Discussionmentioning
confidence: 99%
“…In that situation, online teaching strategies offer students autonomy in the search and construction of their own knowledge, since they have to think critically and acquire the necessary skills for that during that teaching strategy, which requires great reasoning. 11,33 In this sense, basically two trends about the use of the ICTs in education are highlighted: instructionism and constructionism. The first trend privileges information's presentation to the student or as instruction-type interactions, that is, the student answers the proposed questions either having a qualified response or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse sentido, outras investigações sobre esta temática devem ser realizadas e sugere-se enfatizar os recursos tecnológicos e metodologias ativas de aprendizagem. Instigar o uso de ferramentas digitais, como blogs, chat, videoaulas, homepages, e-book interativo, webquest, aplicativos e softwares educacionais e jogos digitais, deve ser incentivado a fim de que essas ferramentas possam ser utilizadas no processo de ensino-aprendizagem possibilitando avanços na qualidade do ensino da graduação em Enfermagem (26) . l ICONCLUSÃO Este estudo permitiu identificar as estratégias de ensino, os recursos didáticos e as ferramentas digitais utilizados na graduação em Enfermagem, de uma instituição pública de ensino, a partir da opinião dos estudantes.…”
Section: Tabela 1 -unclassified